The social and psychological effects of publicly violating a social norm: a field experiment in the Satmar Jewish community - Malovicki-Yaffe, Nechumi; Khan, Sana Adnan; Paluck, Elizabeth Levy (Frontiers in Social Psychology, 2023)
How are ordinary people affected by the experience of stepping out against conventions that are central to their community? We conducted a field experiment in New York City to study Satmar Hasidic women's personal reactions to deviating from their community's high-end clothing norm by wearing an inexpensive plain dress (treatment) vs. carrying a prayer book (normative placebo) for one day. We find that women's experience of deviation from their community norm of high-end dressing was strongly uncomfortable, but was not internalized as new attitudes or self-perceptions. Instead, we find that the experience with deviance mostly affected women's perceptions of their community, in terms of their closeness to the community and to some of its central tenets, and the community norm of high end dressing. In this setting, the experience of individual deviation seems to change perceptions of the context—its norms and our relationship to our community—over perceptions of the self and of deviant action. The results of this study help to map out a theory of community and social change that accounts for individuals' anticipation of deviance and social experiences alone, together, and over time that affect their decisions about whether to participate in change.